Computerized planimetry to assess clinical responsiveness in a phase II randomized trial of topical R333 for discoid lupus erythematosus. (1st June 2018) - Presto, J.K.; Okon, L.G.; Feng, R.; Wallace, D.J.; Furie, R.; Fiorentino, D.; Werth, V.P.
Summary: Background: R333 is a topical janus kinase and spleen tyrosine kinase inhibitor being evaluated for discoid lupus erythematosus (DLE) treatment. There is no validated measure to assess the area of active DLE lesions. Objectives: To evaluate R333 efficacy and assess a technique to measure responsiveness. Methods: Fifty‐four patients with DLE were randomized in a double‐blind design to R333 or placebo. Primary end point was the proportion of patients achieving ≥ 50% decrease in erythema and scale based on lesional Cutaneous Lupus Erythematosus Disease Area and Severity Index TM for all treated lesions at week 4. Two‐dimensional (2D) area measurements for each lesion were recorded at baseline and weeks 1–6. Eighty‐eight photographs (44 pre‐ and 44 post‐treatment) were obtained from the trial and change in size of active areas was analysed by computerized planimetry and physician‐assessed area change (PAAC). Results: Thirty‐six patients were randomized to R333 and 18 patients were randomized to placebo. Primary end point was not achieved. There was a strong association between lesion activity and physician global assessment ( P < 0·001). Photos of 42 patients assessed by computerized planimetry demonstrated excellent inter‐ and intra‐rater reliability. Area change by computerized planimetry showed a strong correlation with PAAC (Spearman r = 0·72). Area change by 2D measurements showed a weak correlation with PAAC (Spearman r = 0·29). Conclusions: Four weeks of R333 treatment did not result in significant improvement in lesion activity. Lesion activity and area change using computerized planimetry are better determinants of responsiveness than area change using 2D measurements.